Hubungan Kecenderungan Gangguan Kepribadian Antisosial dengan Adiksi Online Game pada Remaja Laki-laki Pengunjung Game Centre di Surakarta - Pakha, Dyonisa Nasirochmi; Suwito, Djoko; Afifah, Zulaika Nur (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2014)
Background: Online gaming addiction has become a health issue and brings a negative impact, especially in adolescents. One of the factors that predispose online gaming addiction is the tendency of antisocial personality disorder. The tendency of antisocial personality disorder has symptoms that can lead to addictive attitude. This study aims to determine the correlation between the tendency of antisocial personality disorder and online games addiction in adolescents game center visitor in Surakarta. Methods: This study used an observational analytic with cross sectional approach in ten game centers in Surakarta. Sampling was carried out in July and September 2014 using the inclusion and exclusion criteria that have been determined. The sampling technique used was the total sampling. The independent variable was the tendency of antisocial personality disorder that was measured by The Manson Evaluation Test questionnaire, while the dependent variable was online gaming addiction that was measured by Online Game Addiction Indonesia questionnaire. The data analysis used was Pearson correlation test which Kolmogorov-Smirnov data normality test was previously conducted. Results: This study got 53 samples with a mean age of 17 years, the average score of the tendency of antisocial personality disorder was 29.98Â±9.32, and the average score of online gaming addiction was 18.38Â±5.90. Data normality test showed a significance value of the tendency of antisocial personality disorder = 0.061 (p> 0.05) and for online gaming addiction = 0.200 (p> 0.05), which means that the data distribution of two variables were normal. Pearson correlation test results demonstrate the value of the Pearson correlation coefficient (r) 0562 with a significance value = 0.000 (p <0.05), which means that there was a moderate correlation between the tendency of antisocial personality disorder and online gaming addiction in adolescents game center visitor in Surakarta and the correlation was statistically significant. Conclusions: There is a correlation between the tendency of antisocial personality disorder and online gaming addiction in adolescents game center visitor in Surakarta. Keywords: The tendency of antisocial personality disorder, online gaming addiction, adolescentsÂ